Bili blanket phototherapy - Donel, Jissa (International Journal of Contemporary Pediatrics, 2019)
Jaundice is a common condition in neonates, occurring in 60% to 84% of late term and term infants. Phototherapy is considered as a treatment of choice since many years in the management of unconjugated hyperbilirubinemia. Phototherapy is the use of visible light to treat severe jaundice in the neonatal period. Treatment with phototherapy is implemented in order to prevent the neurotoxic effects of high serum unconjugated bilirubin. Different types of phototherapy delivery system are in use. Bili blanket phototherapy uses fiberoptic systems that reduces or eliminates all of the potential complications of conventional phototherapy and facilitates establishment of an enhanced parent-infant bond.